A Porous Au@Rh Bimetallic Core–Shell Nanostructure as an H2O2‐Driven Oxygenerator to Alleviate Tumor Hypoxia for Simultaneous Bimodal Imaging and Enhanced Photodynamic Therapy. Issue 22 (24th April 2020) - Wang, Jinping; Sun, Jingyu; Hu, Wei; Wang, Yuhao; Chou, Tsengming; Zhang, Beilu; Zhang, Qiang; Ren, Lei; Wang, Hongjun
Abstract: In treatment of hypoxic tumors, oxygen‐dependent photodynamic therapy (PDT) is considerably limited. Herein, a new bimetallic and biphasic Rh‐based core–shell nanosystem (Au@Rh‐ICG‐CM) is developed to address tumor hypoxia while achieving high PDT efficacy. Such porous Au@Rh core–shell nanostructures are expected to exhibit catalase‐like activity to efficiently catalyze oxygen generation from endogenous hydrogen peroxide in tumors. Coating Au@Rh nanostructures with tumor cell membrane (CM) enables tumor targeting via homologous binding. As a result of the large pores of Rh shells and the trapping ability of CM, the photosensitizer indocyanine green (ICG) is successfully loaded and retained in the cavity of Au@Rh‐CM. Au@Rh‐ICG‐CM shows good biocompatibility, high tumor accumulation, and superior fluorescence and photoacoustic imaging properties. Both in vitro and in vivo results demonstrate that Au@Rh‐ICG‐CM is able to effectively convert endogenous hydrogen peroxide into oxygen and then elevate the production of tumor‐toxic singlet oxygen to significantly enhance PDT. As noted, the mild photothermal effect of Au@Rh‐ICG‐CM also improves PDT efficacy. By integrating the superiorities of hypoxia regulation function, tumor accumulation capacity, bimodal imaging, and moderate photothermal effect into a single nanosystem, Au@Rh‐ICG‐CM can readily serve as a promising nanoplatform for enhanced cancer PDT. Abstract : In treatment of hypoxic tumors, oxygen‐dependent photodynamic therapy (PDT) is considerably limited. In this work, a new bimetallic and biphasic Rh‐based core–shell nanosystem (Au@Rh‐indocyanine green‐cell membrane) is developed. Such porous Au@Rh core–shell nanostructures exhibit catalase‐like activity to efficiently catalyze oxygen generation from endogenous hydrogen peroxide to address tumor hypoxia while achieving high PDT efficacy.